2019
DOI: 10.23960/jipt.v6i3.p167-172
|View full text |Cite
|
Sign up to set email alerts
|

Prevalensi Cacing Hati Sapi Perah Pada Peternakan Rakyat Di Provinsi Lampung

Abstract: The study was conducted on dairy cattle livestock at Lampung Province in July - August 2012, aiming to determine the prevalence of liver worms. Disease in livestock caused by liver worm infections are called Fasciolosis. Fasciolosis is an important parasitic disease because it can cause high economic losses. The research method was the census method. Data retrieval were 125 dairy cattle faecal samples from people's dairy farms in Lampung Province. The datas obtained were analyzed descriptively. Examination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 1 publication
0
4
0
6
Order By: Relevance
“…Vaccination has the effect of reducing growth performance due to decreased absorption or digestibility of nutrients in ruminants. Animals that experience nutritional deficiencies can become immunocompromised to delay the immune response time (17).…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination has the effect of reducing growth performance due to decreased absorption or digestibility of nutrients in ruminants. Animals that experience nutritional deficiencies can become immunocompromised to delay the immune response time (17).…”
Section: Discussionmentioning
confidence: 99%
“…Binahong leaves can also be administered through drinking water for broiler chickens. Wahyudi et al [58] found that binahong leaf extract in drinking water did not significantly affect carcass weight but did affect live weight and giblet weight. The dose of binahong leaf extract could be administered up to 150 mg/kg of body weight without impacting live weight, carcass weight, or carcass percentage.…”
Section: Binahong For Livestock Health and Productivitymentioning
confidence: 99%
“…Lokasi kandang dengan sanitasi yang buruk dan keberadaan genangan air juga dapat memungkinkan ternak menderita cacingan seperti cacing hati Fasciola sp. dan infestasi cacing ini dapat menurunkan nilai total eritrosit dan esosinofilia sehingga menyebabkan anemia pada ternak (Siswanto et al, 2018;Hartono et al, 2019).…”
Section: Sanitasi Kandangunclassified